Improvement of the accuracy of the quasigeoid model VIGAC2017 - Hoa, Ha Minh (Vietnam Journal of Earth Sciences, 2018)
As mentioned in (Ha Minh Hoa, 2017), a national spatial reference system will be constructed based on a highly accurate national quasigeoid model with accuracy more than 4 cm. In Vietnam at the present stage there isn’t a detailed gravimetric measurement in mountainous regions and marine area. So with the purpose of improvement of accuracy of the national quasigeoid model VIGAC2017, we only can solve the task of fitting this model to national quasigeoid heights obtained from heights GPS/first, second orders levelling quasigeoid heights through least squares collocation. This scientific article will introduce a first research result for improvement of accuracy of the quasigeoid model VIGAC2017 on the base of it’s fitting to 194 national quasigeoid heights by the least squares collocation. Research results show that accuracy of the quasigeoid model VIGAC2017 will be obtained at level of ±0.058 m and increased to 20.69 %. References Cressie N.A.C., 1993. Statistics for spatial data, John Wiley & Sons. New York, 900p. Ha Minh Hoa, et al., 2012. Research scientific base for perfection of the height system in connection with construction of national dynamic reference system. General report of the science - technological teme of the Ministry of Natural Resources and Environment, Hanoi, 247p. Ha Minh Hoa (Editor), 2016. Research for determination of normal surfaces of sea levels (“zero” depth surface, mean sea surface, highest sea surface) by methods of geodesy, hydrography and geology with serving construction of buildings and planning of coastline in tendency of climate changes”. State techno - scientific theme with code KC.09.19/11-15 in period of 2011-2015, Vietnam Ministry of Science and Technology, Hanoi, 563p. Huang J., Véronneau M., 2013. Contribution of the GRACE and GOCE models to a geopotential - based geodetich vertical datum in Canada. Geophysical Research Abstracts, 15, EGU2013-10164. Iliffe J.C., Ziebart M., Cross P.A., Forsberg R., Strykowski G., Tscherning C.C., 2003. OSGM02: A New model for converting GPS-derived heights to local height datums in Great Britain and Ireland. Survey Review, 37(290), 276-293. Marcin Ligas, Marek Kulczycki, 2014. Kriging approch for local height transformations. J, Geodesy And Cartography, Polish Academy of Sciences, 63(1), 5-37, Doi: 10,2478/geocart-2014-0002. Metin Soycan, 2014. Improving EGM2008 by GPS and leveling data at local scale. BCG - Boletin de Ciências Geodésicas Sec, Artigos, Curitiba, 20(1), 3-18, on - lineversion, ISSN 1982-2170. Doi,org/10,1590/S1982-21702014000100001. Moritz H., 1980. Advanced Physical Geodesy. Herbert wichmann Verlag Karlsruhe, Abacus Press Tunbridge Wells Ken, 512p. Quasigeoid of the Federal Republic of Germany GCG2016. Federal Agency for Cartography and Geodesy, www,geodatenzentrum.de. Roman D.R., Wang Y.M., Saleh J., Li X., 2010. Geodesy, Geoids & Vertical Datums: A Perspective from the U,S, National Geodetic Survey. FIG Congress 2010, Sydney, Australia, April 2010, 11-16. Schabenger O., Gotway C.A., 2005. Statistical methods for spatial data analysis. Chapman & Hall/CRC, New York, ISBN 1-58488-322-7, 488p. Smirnov N.V., Belugin D.A., 1969. Probability theory and mathematical statistics in applying to geodesy. Moscow, Nedra, 379p.